2.8k views
4 votes
9j + 6 = -4 + 10j
j= Help ASAP

2 Answers

4 votes
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

9*j+6-(-4+10*j)=0

Step by step solution :

STEP
1
:
Solving a Single Variable Equation

1.1 Solve : -j+10 = 0

Subtract 10 from both sides of the equation :
-j = -10
Multiply both sides of the equation by (-1) : j = 10



j = 10
User Twhb
by
6.0k points
3 votes

Answer:

10=j

Explanation:

i did the math and typed it in and clicked the "add answer" button

User Jory Cunningham
by
5.5k points